[Rezension von: Birkett, Chris, Bill Clinton at the church of baseball : the presidency, civil religion, and the national pastime in the 1990s] - Young, Samuel L. (A journal of church and state, 2025)
This book examines the relationship between two quintessentially American institutions—the presidency and Major League Baseball—during the 1990s. Scholars